Detection and characterisation of defects in directed energy deposited multi-material components using full waveform inversion and reverse time migration. Issue 4 (2nd October 2022) - Rao, Jing; Sing, Swee Leong; Lim, Joel Choon Wee; Yeong, Wai Yee; Yang, Jizhong; Fan, Zheng; Hazell, Paul
ABSTRACT: Directed energy deposition (DED) is capable in producing complex or high-value components with good mechanical properties. Despite these potential advantages, the quality and integrity of multi-material DED parts, remains a challenging issue that limits its wide applications. Material porosity in multi-material components is detrimental since it may lead to premature structural failure. This paper proposes a two-stage ultrasonic method to characterise the internal structure to enhance the understanding of the process parameters on material porosity. In this method, the low-frequency model building aims at reconstructing background structure and the high-frequency imaging targets at small defects. The first stage is based on the gradient sampling full-waveform inversion for the estimation of the velocity model, which is then used as the initial model for the reverse time migration for reflectivity. The experimental results show that accurate reconstructions of the interface between two materials and defects in multi-material DED components can be achieved.